Martyrdom: canonisation, contestation and afterlives - Saloul, Ihab ca. 20./21. Jh.; Henten, Jan Willem van (Heritage and memory studies, 2020)
"The idea of writing this book first emerged during the "International Expert Meeting, Canonisation and Cross-Cultural Martyrdoms", which was held in Amsterdam on 8-9 December 2006." (Acknowledgments)